Unique Design of Learning Studio Spaces: A Case Study of The Department of Applied Design and Fine Art Kabale University. - Akatwijuka, Onesmus (Kabale University, 2023)
Every design institute must have modified art studios which are designed in order to manage or facilitate experimental or practical and revisable or theoretical visual artist' work comfortably. (Sjoholm, 2013). The literature review of the study is based on what an art studio is, its importance, features and various types of art studios as well as the methods used in designing art studio space using the objectives of the study. The designing of learning spaces or Art Studios will be supported by known scholars who explain the Art Studio space and interior space management using the objectives of the study. According to (Wikipedia, 2018), A studio is an artist or worker's workroom. It can be for the purpose of acting, architecture, painting, pottery (ceramics), sculpture, origami, woodworking, scrapbooking, photography, graphic design, filmmaking, animation, industrial design, radio or television production broadcasting or the making of music. The term is also used for the workroom of dancers, often specified to dance studio (Eshelman Evans, 2002). A studio art classroom has unique learning needs and safety considerations (Bartel, 2007). Any Interior work done without consideration of space management principles can therefore not be called perfect, which should not even be useful and also durable or durable but not useful, or either having both these should be without beauty. (Slotkis, 2002). Therefore, understanding the concept of "place" provides an important framework for the way people form relationships with the built environment. The concepts of "third place," place attachment, and distance each have an impact on how designed social spaces are used and liked. Designers can encourage walking and the use of social spaces among residents (Campbell, 2014 ). The evolution of the artist's studio, from renaissance Bottega to assembly line that, the French term for studio, atelier, in addition to designating an artist's studio is used to characterize the studio of a fashion designer. The studio of any artist, especially from the 15th to the 19th centuries, characterized all the assistants, thus the designation of paintings as "from the workshop of..." or "studio of..." In contemporary, English language use, "atelier" can also refer to the Atelier Method, a training method for artists that usually takes place in a professional artist's studio. (Sjoholm, 2013)